Estimating Low- and High-Cyclic Fatigue of Polyimide-CF-PTFE Composite through Variation of Mechanical Hysteresis Loops; Materials; Vol. 15, iss. 13 - Panin A. V. Alexey Viktorovich; Bogdanov A. A. Aleksey Alekseevich; Eremin A. V. Alexandr Vyacheslavovich; Buslovich D. G. Dmitry Gennadjevich; Alekseenko V. O. Vladislav Olegovich (2022, 2022)
Title screen